Immigrant specificity and the relationship between trade and immigration: Theory and evidence - Harry P. Bowen; Jennifer Pédussel Wu (Hochschule für Wirtschaft und Recht Berlin, IMB Institute of Management Berlin, 2012)
Studies routinely document that the nature of immigrant employment is largely specific: it often concentrates in non-traded goods sectors and many immigrants often have low inter-sectoral mobility. We consider these observed characteristics of immigrant employment for the question of how immigration affects a nation's pattern of production and trade. We model an economy producing three goods; one is non-traded. Domestic labor and capital are domestically mobile but internationally immobile. Any new wave of immigration is assumed to comprise some workers who will become specific to the nontraded goods sector. The model indicates that the output and trade effects of immigration depend importantly on the sectoral pattern of employment of existing and new immigrants. Empirical investigation in a panel dataset of OECD countries supports the models prediction that immigration raises the output of non-traded goods. Consistent with the model, we also find that immigration and trade are complements. The implications of the model and empirical findings for immigration policy are then discussed. – – Diverse Studien belegen, dass die Beschäftigung von Immigranten sehr spezifisch ist: Sie beschränkt sich häufig auf Anstellungen in der Produktion nicht gehandelter Waren. Der Großteil der Immigranten zeigt dabei nur eine geringe Mobilität zwischen den Sektoren. Unter Berücksichtigung dieser beobachteten Besonderheiten bei der Beschäftigung von Immigranten untersuchen wir die Auswirkungen von Immigration auf die Handels- und Produktionsstrukturen eines Staates. Unser Modell umfasst eine Volkswirtschaft, die drei Güter produziert; eines davon wird nicht gehandelt. Heimische Arbeitskräfte sind innerstaatlich mobil, aber immobil auf internationaler Ebene. Es wird angenommen, dass jede neue Immigrationswelle Arbeiter mit sich bringt, welche in Wirtschaftszweigen nicht gehandelter Güter beschäftigt werden. Das Modell zeigt, dass die durch Immigration verursachten Auswirkungen auf Produktion und Handel stark von branchenspezifischen Beschäftigungsmustern vorhandener und neuer Immigranten abhängig sind. Die empirische Untersuchung des prognostizierten Zusammenhangs von Immigration und Handelsströmen basiert auf einem Datensatz von OECD Ländern und bekräftigt die Vorhersage, dass Handel und Immigration Komplemente sind. Abschließend wird die Bedeutung des Modells und der empirischen Ergebnisse für die Gestaltung von Immigrationspolitik diskutiert.
Keywords: 330